Self-compassion and resilience in parents of children with special needs: The mediating role of hope - Aydın Sünbül, Zeynep; Aslan Gördesli, Meltem (Cukurova University, 2020)
The purpose of this study was to explore hope as a mediator in the relationship between self-compassion and resilience in parents of children with special needs. Participants of the study were 120 parents (95 females, 25 males). The preliminary results showed that resilience scores of the participants don't vary as a function of gender, income, education level and age. The results of the path analysis yielded that the model fit indices of the proposed model are perfect (chi(2)/df=.03, p<.001; RMSEA=.00; CFI=1.00; TLI= 1.00; GFI=.99). Examination of the relationships between the variables yielded that there are significantly positive connections between selfcompassion and hope and also between hope and resilience. The model was found to explain a 5% variance in hope scores and 16% variance in resilience scores of parents of children with special needs. These results were discussed in line with the relevant literature as well as possible interventions for cultivation of resilience in these parents.

Bu çalışmanın amacı, özel gereksinimli çocukların ebeveynlerinde öz-şefkat vepsikolojik sağlamlık arasındaki ilişkide umudun aracı rolünü incelemektir. Çalışmanınkatılımcıları 120 ebeveynden (95 kadın, 25 erkek) oluşmaktadır. Yapılan ön analizlerpsikolojik sağlamlığın cinsiyet, gelir, eğitim düzeyi ve yaşa göre anlamlı düzeydefarklılaşmadığını ortaya koymuştur. Yol analizi sonuçları, önerilen modelin model uyumindekslerinin mükemmel olduğunu göstermiştir (?2/ df = .03, p ?.001; RMSEA = .00; CFI= 1.00; TLI = 1.00; GFI = .99). Değişkenler arasındaki ilişkilerin incelenmesi sonucunda,öz-şefkat ve umut arasında ve umut ile psikolojik sağlamlık arasında anlamlı derecedepozitif yönde ilişkiler olduğu bulunmuştur. Modelin özel gereksinimli çocuklarınebeveynlerinin umut puanlarında %5 ve psikolojik sağlamlık puanlarında %16düzeyinde bir varyans açıkladığı bulunmuştur. Bu sonuçlar, ilgili literatür ve buebeveynlerde psikolojik sağlamlığı geliştirmeye yönelik olası müdahalelerdoğrultusunda tartışılmıştır.
Özel gereksinimli çocukları olan ebeveynlerde öz-şefkat ve psikolojik sağlamlık: Umudun aracı rolü
Keywords: Self-Compassion; Resilience; Hope; Parents of Children With Special Needs; Öz-Şefkat; Psikolojik Sağlamlık; Umut; Özel Gereksinimli Çocuklara Sahip Ebeveynler